Identification of Exiguobacterium acetylicum by a double real- time polymerase chain reaction assay - GAO Cancan; LIU Jiamei; LI Junjie; LU Zhaoxin; LÜ Fengxia; ZHANG Chong; ZHAO Haizhen; BIE Xiaomei (浙江大学学报. 农业与生命科学版)
Exiguobacterium sp. has been figured out to be the main spoilage bacteria on many kinds of food, and it has the potential to be the main spoiler. Bacteria Exiguobacterium have already been isolated from extreme environment and they have evolved and acquired some resistance including thermotolerance, cold resistance, alkali resistance, and osmotolerance. The Exiguobacterium can normally metabolize under 4℃ storage temperature. Further, Exiguobacterium has strong proteolysis ability to damage nutrient and food, and it can form biofilm, not only increasing the resistance to detergents and preservatives, but also consuming nutrients to grow and reproduce. The present study aims to establish a rapid identification method of Exiguobacterium acetylicum based on a double real-time polymerase chain reaction (RT-PCR).The study took the genes P401_RS0117025 and oxi_50582462, which were screened in the early experiment and were specific to Exiguobacterium sp. and E. acetylicum respectively, as detection targets. The specificity of the PCR assay was verified with the DNA of 12 E. acetylicum strains and 14 non-E. acetylicum strains; the effectiveness of the assay was evaluated by the foundation of standard curve, as well as its repeatability. The sensitivity of different DNA and cell concentrations was identified.The results demonstrated that the specific genes and primers of the early experiment were both well-specific. The specific evaluation experiment results showed that the probes T-291 and T-2B were also well-specific. The R2 values of standard curve were 0.994 and 0.999, respectively, indicating that the assay was credible, and the RT- PCR showed high repeatability. When DNA of different concentrations were added as templates, there was no obvious different in standard deviation of threshold (Ct), and the coefficient of variation of the same concentration was fluctuation during 0.51 to 1.12. Even though at 1.629×10－4 ng/μL, its repeatability was well maintained, which indicated that the assay could show high repeatability at the low DNA concentration. The sensitivity-evaluation showed that the DNA detection limit of the assay was 1.629×10－7 ng/μL, and the detection limit of pure bacteria colonies was 3.4 CFU/mL without enrichment culture. In addition, the high-sensitivity resulted in its outcoming of short-time cast, for it did not need the step of enrichment culture, which was different from other studies. Finally, the mathematical relationship between Ct and Nt (colony-forming units, CFU) was developed by software Origin 9. It was Ct=－1.759×Nt+31.678, the R2 value of which was 0.939. When applied to the fresh-cut leafy vegetables, the assay and the equation could detect rapidly and accurately the CFU on them.In sum, this study establishes an accurate, sensitive and efficient double RT- PCR assay to detect quantitatively food spoilage bacteria E. acetylicum. It lays a theoretical basis for food shelf- life prediction, and provides some references to the supply chain of fresh-cut vegetables.